Celiac disease and pregnancy in Indian scenario - Verma, Anupam; Tyagi, Preeti; Singh, Anu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Celiac disease is a chronic lifelong inflammatory condition of gastrointestinal tract specifically the small intestine. We report a case of pregnancy outcome in a patient with celiac disease (gluten sensitive enteropathy) diagnosed during the investigations of recurrent abortions and intermittent diarrhoea since childhood. A 32 years old patient who had four abortions and loss of a premature baby was diagnosed as celiac disease during investigations of recurrent abortions and diarrhoea since childhood. After stabilisation of disease she conceived spontaneously. Patient had regular follow up in some private institute. She was referred to our hospital as a case of IUGR with color Doppler changes with breech presentation with sluggish fetal movements at 37 weeks and emergency caesarean section was performed. A male fetus with 2.25 kg AS 7, 9 at birth was delivered. The cause of her recurrent pregnancy losses and previous preterm birth was celiac disease. Celiac disease (CD) is an immune-mediated enteropathy caused by a permanent sensitivity to gluten in genetically susceptible individual. It may also lead to serious maternal and fetal complications because of systemic effects of disease however a successful pregnancy outcome is possible when pre-gestational diagnosis is made and proper management of disease during pregnancy is achieved.